PENGARUH SUKU BUNGA DEPOSITO, PDB DAN VOLUME PERDAGANGAN SAHAM TERHADAP IHSG DI INDONESIA ( Pengguna Model ARCH-GARCH, Kointegrasi dan ECM ) - Bahtiar Usman (Media Riset Bisnis & Manajemen, 2007)
The Study purpose is to choose the best model to predict changes in Indek Harga Saham Gabungan at Indonesia capital market.  The resarch use IHSG, Stock Trading Volume, Interest Rate and GDP data from 1992: 01-2005: 12.  The study find that Arch-Garch is the best model to predict changes in IHSG rather than ECM because this model fit to data which contains heterochasticity where prior error volatility occurred.  The results are, interest rate have negative effect to IHSG while Stock Trading Volume and GDP have a positive effect with R2  around 87.27%.